Rapid induction of selective transcription by auxins. - Hagen, G (1985)
Nuclei isolated from excised soybean plumules that were treated with 2,4-dichlorophenoxyacetic acid (2,4-D) were active in transcription of four auxin-regulated genes or DNA sequences, which have been described previously (G. Hagen, A. Kleinschmidt, and T. Guilfoyle, Planta 162:147-153, 1984). The rates of transcription of the auxin-responsive sequences were 10- to 100-fold greater with nuclei isolated from auxin-treated plumules than with those from untreated plumules. The transcriptional response was also observed with hypocotyls of intact soybean seedlings and hypocotyl sections, as well as with green bean and mung bean plumules that were treated with 2,4-D. Other auxins, including 2,4,5-trichlorophenoxyacetic acid, alpha-naphthaleneacetic acid, and indole-3-acetic acid, also induced the transcriptional response. Increased transcription rates were observed within 5 min after application of auxins to excised plumules, and half-maximal to maximal transcription rates were achieved by 15 min after application of auxins. As little as 10(-7) to 10(-8) M 2,4-D induced a transcriptional response, but maximal transcription rates were achieved at 10(-3) M 2,4-D. Brief treatment with the protein synthesis inhibitor cycloheximide did not inhibit the induction of transcription by auxins. These results clearly demonstrated that auxin-regulated gene expression is under rapid transcriptional control.